Facile synthesis of oriented zinc oxide seed layer for the hydrothermal growth of zinc oxide nanorods - Farhad, SFU; Tanvir, NI; Bashar, MS; Hossain, MS; Sultana, M; Khatun, N (Bangladesh Journal of Scientific and Industrial Research, 2018)
Oriented zine oxide (ZnO) seed layers were deposited by simple drop casting of zinc acetate dihydrate (ZAD) solution on glass substrates at room temperature followed by a post-heat treatment at 250 oC. X-ray diffraction (XRD) analyses revealed that ZAD solutions with concentration 0.0025 – 0.0100 M produced amorphous type thin films, whereas 0.0200 M ZAD solutions produced ZnO seed layers with a preferential c-axis texturing.The Scanning Electron Microscopy (SEM) analyses evident that the morphology of ZnO seed layer surface is compact and coherently carpets the underlying glass substrate. ZnO nanorods were then grown by hydrothermal method atop the ZnO seeded and non-seeded substrates. The presence of ZnO seeding layers was found to be beneficial for growing ZnO NRs films vertically. The optical bandgap of ZnO seed and ZnO NR were estimated to be in the range of 3.40 – 3.95 eV and 3.20 – 3.25 eV respectively by using UV-VIS-NIR diffuse reflection spectroscopy. The room temperature photoluminescence analyses revealed that nanostructured ZnO films exhibit a sharp near-band-edge luminescence peak at 380 nm consistent with the estimated optical band gap and the ZnO nanorod arrays are notably free from defect-related green-yellow emission peaks. Bangladesh J. Sci. Ind. Res.53(4), 233-244, 2018